THE EFFECT OF INFLUENCER MARKETING AND BRAND AWARENESS ON GEN Z'S FOOD PRODUCT PURCHASE DECISIONS, WITH CUSTOMER ENGAGEMENT AS AN INTERVENING VARIABLE - Rey Disna Pramestia; Brahma Wahyu Kurniawan (SOSIOEDUKASI, 2026)
This study aims to examine the influence of influencer marketing and brand awareness on Generation Z’s food product purchase decisions, as well as to analyze the role of customer engagement as a mediating variable in the relationship between these variables. This study employs a quantitative approach using a survey method. The research subjects are Generation Z individuals in Kediri City who have purchased food products based on influencer recommendations on social media. The sampling technique used purposive sampling with a sample size of 96 respondents determined based on the Lemeshow formula. Data collection was conducted through the distribution of a questionnaire using a 1–5 Likert scale with a total of 16 research indicators. The data were analyzed using the SEM-PLS method with the assistance of the SmartPLS application to test the validity and reliability of the research instruments. The results indicate that brand awareness and customer engagement have a positive and significant influence on Generation Z’s food product purchase decisions. Influencer marketing was found to enhance customer engagement but does not exert a significant direct influence on purchase decisions. Furthermore, customer engagement acts as a mediating variable that strengthens the influence of influencer marketing and brand awareness on purchase decisions.